Encyclopedia of chemical technology : sulfonation and sulfation to thorium and thorium compounds (New York : John Wiley, 1983)
Chemistry and Physics
Keywords: Encyclopedias; Chemical technology; Chemistry, Technical-Encyclopedias; Sulfation; Thorium compounds